Crystalline and molecular structure of novel anion-radical salt (N-Et-Pz)(TCNQ)₃ (Pz is pyrazine) - Ziolkovskiy, D.V.; Kravchenko, A.V.; Starodub, V.A.; Kazheva, O.N.; Khotkevich, A.V. (Functional Materials, 2005)
Crystalline and molecular structure of previously synthesized by the authors anion-radical salt (ARS) 7,7,8,8-tetracyanoquinodimethane (TCNQ) of an unusual [N-(H₅C₂)-Pz](TCNQ)₃ composition (where Pz is pyrazine) has been determined. The structure of the given ARS is also unusual because unlike most of structures known it consists of bulks formed by two А and С TCNQ types, particles of the third В type being located at the angle of 117.7 and respectively 117.4 degrees relatively to them. С type particles interact appreciable with pyrazine cations through pyrazine non-alkylated nitrogen atom. В-type particles as well as TCNQ particles in columns, possess an appreciable charge (about -0.3).Such a peculiarity of structure renders ARS electronic system some what two-dimensional that is unusual for TCNQ ARS and agrees with the electrophysical measurements.